A Variety of Functional Devices Realized by Ionic Nanoarchitectonics, Complementing Electronics Components. (27th October 2021) - Terabe, Kazuya; Tsuchiya, Takashi; Tsuruoka, Tohru
Abstract: To realize the continuous development of information and communication equipment, it is also important to develop devices with new operating principles that overcome the functional and performance limitations of conventional electronics devices, such as transistors made of semiconductor materials. One group of devices that hold this promise is nanoionics devices that operate by using local ion transport and electrochemical reaction in solids. A number of nanoionics devices that control nanoelectrochemical phenomena through the use of ionic nanoarchitectonics have been created. Here the use of ionic nanoarchitectonics to locally control ion transport and electrochemical reactions through the use of ion conductors or mixed conductors as device materials is described. Further, the structures of nanoionics devices created by using the nanoarchitectonics, as well as their various electrical, magnetic and optical functionalities are introduced. It is expected that such nanoionics devices will complement conventional electronics devices, and make possible the further development of information and communication technologies. Abstract : It is important to develop devices that overcome performance limitations of conventional semiconductor devices. One group of devices that hold this promise are nanoionics devices that operate by local ion transport and electrochemical reaction. A number of nanoionics devices have been created through the use of ionic nanoarchitectonics. It is expected that such nanoionics devices will complement conventional semiconductor devices.